Digital Teaching Material in Learning Content of Rewanda Traditional Value in Goa Kreo Semarang to Improve Historical Awareness of Students At 12 SMA Negeri - Rian Agus Mulyawan; Leo Agung S; Djono Djono (Universitas Sebelas Maret, 2020)
The purpose of this study is to explain the process of cultivating historical awareness of the value of the rewanda custom in the cave creo semarang in history learning at SMA Negeri 12 Semarang, explaining how historical awareness among students at SMA Negeri 12 Semarang, explains the relevance between Adat Rewanda and Historical Awareness in learning and explaining how to integrate the traditional values of rewanda in Goa Kreo Semarang with history learning at SMA Negeri 12 Semarang. Researchers used qualitative research methods with descriptive and phenomenological approaches. The results of this study indicate that the cultivation of historical awareness of the customary value of rewanda in the cave creo semarang is appropriate, proven by the existence of a Learning Implementation Plan and Syllabus in the 2013 Curriculum, the implementation of learning, evaluation and historical awareness of students which is shown mostly from the results of student interviews, namely understanding. There are factors that affect the level of students' historical awareness, among others, the history of teacher competence, existing learning, and the environment. The facilities used in the cultivation of historical awareness are supported by learning and extracurricular resources.